2021
DOI: 10.11646/zootaxa.4933.1.4
|View full text |Cite
|
Sign up to set email alerts
|

The crystalline waters of the Bodoquena Plateau revealed Hypostomus froehlichi (Siluriformes: Loricariidae), a new armored catfish from the rio Paraguay basin in Brazil

Abstract: The menaced and poorly-known waters of the Bodoquena Plateau revealed a new resident, the stunning Hypostomus froehlichi sp. n., a large-sized armored catfish, which is finally described after more than twenty years since its discovery. The Bodoquena Plateau is drained by the rio Paraguay basin, and is located in the state of Mato Grosso do Sul, Brazil. The new species differs from its congeners on the Bodoquena crystalline waters by having teeth with morphological and numerical variation in adult specimens. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 856 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…This example was that of larger body sizes among males for H. hermanni, as documented by Nomura and Mueller (1980). Dimorphism within the genus Hypostomus is apparently uncommon given that studies have concluded a lack of sexual dimorphism for H. commersonii (Goulart and Verani 1992), H. affins and H. luetkeni (Mazzoni and Caramaschi 1995), H. velhochico (Zawadzki et al 2017), H. subcarinatus (Zawadzki et al 2019), and H. froehlichi (Zawadzki et al 2021). Our work supports the pattern of larger body size in males for congeneric H. hermanni documented by Nomura and Mueller (1980) as well as the >100-year-old report by Miranda Ribeiro (1918) of enlarged fins in males of H. albopunctatus (Zawadzki et al 2020).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This example was that of larger body sizes among males for H. hermanni, as documented by Nomura and Mueller (1980). Dimorphism within the genus Hypostomus is apparently uncommon given that studies have concluded a lack of sexual dimorphism for H. commersonii (Goulart and Verani 1992), H. affins and H. luetkeni (Mazzoni and Caramaschi 1995), H. velhochico (Zawadzki et al 2017), H. subcarinatus (Zawadzki et al 2019), and H. froehlichi (Zawadzki et al 2021). Our work supports the pattern of larger body size in males for congeneric H. hermanni documented by Nomura and Mueller (1980) as well as the >100-year-old report by Miranda Ribeiro (1918) of enlarged fins in males of H. albopunctatus (Zawadzki et al 2020).…”
Section: Discussionmentioning
confidence: 93%
“…2019), and H. froehlichi (Zawadzki et al. 2021). Our work supports the pattern of larger body size in males for congeneric H. hermanni documented by Nomura and Mueller (1980) as well as the >100‐year‐old report by Miranda Ribeiro (1918) of enlarged fins in males of H. albopunctatus (Zawadzki et al.…”
Section: Discussionmentioning
confidence: 99%